Analisis Pengaruh Sifat Fisik dan Kekuatan Mekanik Bahan RAP (Reclaimed Asphalt Pavement) Terhadap Nilai Kepadatan dan CBR (California Bearing Ratio) - Fitri Eska Rachmawati, Chanifah; , Ir. Agus Riyanto, MT; , Ir. Sri Sunarjono, MT, Ph.D (2016)
Now, RAP is currently used for recycling job in the cold mix processed. Quality from mix of RAP don't competitive when compared with hot mix. This condition from RAP is already degraded aggregate, changes of texture from aggregate, aged aggregate. This condition resulted mix of RAP has a low density. Based on the problem then need to analyze the influence of the physical properties and mechanical strength against density and CBR between RAP and fresh aggregate. This research used test laboratorium method with using RAP original and fresh aggregate. This research didn't use any added ingredients. The kind of examination in this research as physical properties (sieve analysis, specific gravity and absorpsi, shape of aggregate, sand equivalent, weight content). Mechanical strength as (Los Angeles, Aggregate Impact Value (AIV), modified AIV, Aggregate Crushing Value (ACV), Ten Percent Fines Value (TPFV). Appart of them there's a test compaction and CBR. After that the results from test in laboratory, the data to analyzed and compared between RAP and fresh aggregate for to find out how the influence of the physical properties and mechanical strength to the density and CBR. Based on the results of the physical properties of the asphalt and cluster to wrap aggregate surface may change to the distribution of aggregate, reduces water absorption, to reduces the movement of aggregate when to fill void in mixture. Based on the results of the mechanical strength of the asphalt and cluster to wrap aggregate surface to positive role to help the RAP in reducing from load placed in the form of a clash, collision, and the pressure. Based on the results of the analysis of the influence of the physical properties and mechanical strength of the density and CBR to concluded the physical properties directly influence the density and CBR. And to assisted with the mechanical strength is good, then will to produce mix capacity a good, because the capacity of a material can't if only rely on mechanical strength. Physical properties and mechanical strength of the material to work together to create density and high capacity. Based on the results of the comparative analysis of performance (density and CBR) concluded that the performance from RAP lower than fresh aggregate performance.